The synthesis of a pixelated metamaterial cross-polarizer using the binary wind-driven optimization algorithm - Ranjan, Prakash; Mahato, Santosh Kumar; Choubey, Arvind; Sinha, Rashmi; Peraza-Vázquez, Hernán; Barde, Chetan; Peña-Delgado, Adrián; Roy, Komal (Journal of computational electronics, 2022)
In this paper, the synthesis of two wideband metamaterial cross-polarizers (MCPs) is proposed. The synthesis of the proposed MCPs is done using the binary wind-driven optimization (BWDO) technique, which is an advanced version of the wind-driven optimization (WDO) technique. The maximum number of iterations is determined to achieve the desired wideband responses. Model-I is obtained after 10 iterations, which achieves a −10 dB conversion bandwidth of 5.09 GHz, ranging from 6.59 to 13.70 GHz, with three polarization conversion ratio (PCR) peaks at 7.6, 9.8 and 11.9 GHz and PCR percentage of 99.89, 99.90 and 99.02%, respectively. Similarly, Model-II is obtained after 18 iterations, which achieves a −10 dB conversion bandwidth of 5.67 GHz, with a range of 5.96 to 12.80 GHz and three PCR peaks at 6.8, 8.5 and 11.9 GHz with PCR percentage of 99.85, 99.88 and 99.29%, respectively. The wideband cross-polarization mechanism is investigated by the analysis of wideband MCPs with two different techniques: first, with the help of effective electromagnetic (EM) parameters ε eff and μ eff , and secondly with the help of current distribution techniques. The proposed MCPs are fabricated on flame-retardant (FR-4) substrate and tested inside an anaerobic chamber. The tested and simulated results obtained are very close to each other, with only a small variance with respect to fabrication tolerance. Finally, the proposed MCPs are compared with previously reported MCPs.